Cornstarch, wheat flour and cassava starch as binders for Labahita (Surgeon) fish sausage - Caldito, Aida C.; Acevedo, Teresita P. (1963)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fishery processing